A Formação Continuada De Professores De Ciências Humanas Para Uma Consciência Do Ensino Da Competência Leitora (PERcursos Linguísticos, 2023)
The formation of teachers in Brazil presents a dichotomy between models of areas of knowledge and models of pedagogical-didactic formation. For a long time, these models were distant, however, with interdisciplinary methodologies in large-scale tests to measure student learning (SAEB and ENEM), more and more, it is necessary to rethink continuing education in Brazil. Teachers need a theory vs. practice, in order to improve the teaching-learning of students. Associated with this, it is necessary to engage all teachers in the areas of knowledge at school to teach reading, considering that the scenario of proficiency and reading comprehension in Brazil is asymmetrical for age/grade in basic education. This situation is aggravated when the function of reading at school falls only to the Portuguese teacher. Considering this educational situation, this article presents a gamified methodology, as a training proposal, developed for teachers of Human Sciences (History and Geography) to raise awareness of the reading process and reading comprehension of students. This training proposal serves so that other teacher-trainers can replicate it, with the aim of reducing the asymmetry of reading proficiency in Brazil.